Recommendations for the use of Eco-Parking in an Urban Environment (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The article examines the problems of creating and using traditional parking spaces and their replacement with modern environmentally friendly eco-parking, their impact on urban space, the city's ecology and the well-being and health of the population, as well as issues of economic development and the technological feasibility of using eco-parking.